2010
DOI: 10.1007/s00420-010-0506-6
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and work participation: a systematic review

Abstract: PurposeSelf-regulatory processes play an important role in mediating between the disease and the health outcomes, and potentially also work outcomes. This systematic review aims to explore the relationship between illness perceptions and work participation in patients with somatic diseases and complaints.MethodsThe bibliographic databases Medline, PsycINFO and Embase were searched from inception to March 2008. Included were cross-sectional or longitudinal studies, patients with somatic diseases or complaints, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 37 publications
3
53
1
2
Order By: Relevance
“…An emerging body of research has suggested that beliefs about illness (illness perceptions) are important influences on clinical and work outcomes for those with back pain (e.g., Foster et al 2008;Main, Foster & Buchbinder 2010;Hoving et al 2010;Giri et al 2009). One theoretical model which has been widely established as a useful framework through which to explore illness perceptions is the Common-Sense model of self-regulation of health and illness (the CSM; e.g., Leventhal, Nerenz & Steele 1984).…”
Section: Case Study 1 Collaborative Working In Cancer Care: An Exampmentioning
confidence: 99%
“…An emerging body of research has suggested that beliefs about illness (illness perceptions) are important influences on clinical and work outcomes for those with back pain (e.g., Foster et al 2008;Main, Foster & Buchbinder 2010;Hoving et al 2010;Giri et al 2009). One theoretical model which has been widely established as a useful framework through which to explore illness perceptions is the Common-Sense model of self-regulation of health and illness (the CSM; e.g., Leventhal, Nerenz & Steele 1984).…”
Section: Case Study 1 Collaborative Working In Cancer Care: An Exampmentioning
confidence: 99%
“…As indicated by our study and others, communication is a key to solve work-related problems [31,32]. In the occupational health literature on chronic disease, several interventions show positive results in improving work participation including so-called vocational rehabilitation strategies that include coaching employees to have effective communication with their employer [33] and also empowerment of employees in difficult work situations [31,34]. Supporting employees with RA to actively deal with their issues at work may not only increase their own skills but will also allow the work environment to provide better support as they are kept better informed about illness-related problems or needs by the employees.…”
Section: Discussionmentioning
confidence: 79%
“…Although low back pain (LBP) is still the prime interest of most authors [25,26,34,[40][41][42][43][44][45], other disorders such as tenosynovitis, epicondylitis [46] and whiplash [47,48], or other anatomical sites such as the neck [49], upper limbs [50] and shoulders [50,51], caught some authors' attention. We observed that when the focus was the prevention of prolonged disability, the questions tackled were general, regardless of disability site or type [52][53][54][55], and that the studies described either the best available evidence on RTW interventions [50,[56][57][58][59][60][61][62][63][64][65][66] or appropriate work-disability measurement processes [67]. Twenty-seven theoretical articles were retrieved from 17 different scientific journals and one handbook.…”
Section: Description Of the Literature Reviewedmentioning
confidence: 99%